ASPEK BIOLOGI CUMI-CUMI (Loligo sp.) YANG TERTANGKAP OLEH NELAYAN DI PERAIRAN MANOKWARI - Amida E Ayorbaba; Nurhani Widiastuti; Arnoldus S. Ananta; Paulus Boli (Jurnal Sumberdaya Akuatik Indopasifik, 2019)
Squid (Loligo sp.) is one of the fisheries commodities caught in Manokwari waters. The aim of this study was to determine the biological aspects of Loligo sp. including the sex ratio, size distribution, growth pattern, and the lengthy relationship of Loligo sp. from Manokwari waters. This research was conducted in January until March 2017, in three landing sites of squid (Loligo sp) namely Fanindi Pantai, Borobudur and Arowi village. The method used is observation technique in the laboratory includes measurements of length and weight to find out the size distribution and growth pattern of captured Loligo sp. and surgery to determine the sex ratio. The male-female sex ratio of Loligo sp. was 1.3: 1.0 with a range of coat length and wight dominated by male. The growth pattern of Loligo sp in Manokwari waters is negative allometric, where the length increase is faster than the weight gain.